Characterization of atherosclerotic plaques in blood vessels with low oxygenated blood and blood pressure (pulmonary trunk): role of growth differentiation factor-15 (GDF-15) - Bonaterra, Gabriel; Struck, N.; Zuegel, S.; Schwarz, A.; Mey, L.; Schwarzbach, H.; Strelau, Jens; Kinscherf, R. (BMC cardiovascular disorders, 2021)
Growth differentiation factor (GDF)-15 is linked to inflammation, cancer, and atherosclerosis. GDF-15 is expressed in most tissues but is extremely induced under pathological conditions. Elevated serum levels are suggested as a risk factor and a marker for cardiovascular diseases. However, the cellular sources and the effects of GDF-15 on the cardiovascular system have not been completely elucidated including progression, and morphology of atherosclerotic plaques. Thus, this work aimed to characterize the influence of GDF-15 deficiency on the morphology of atherosclerotic plaques in blood vessels with low-oxygen blood and low blood pressure as the pulmonary trunk (PT), in hypercholesterolemic ApoE−/− mice.